BARIUM CONCENTRATION IN DEEP SEA SURFACE SEDIMENTS FROM TOMINI BASIN: VERTICAL DISTRIBUTION AND OCCURRENCE - DIDA KUSNIDA; P.H. WIJAYA WIJAYA; J. WIDODO WIDODO (Balai Besar Pengujian Mineral dan Batubara tekMIRA, 2010)
The concentrations of trace elements (Th, Zr, Ba, Ce, Nb and Sr) in the sediments core from Tomini Basin, Sulawesi were studied to establish their vertical distributions and occurrence. However, the highest concen- tration of trace elements was dominated by barium (>300 ppm). Results indicate that barium composition in the surface sediments generally increase downward. Vertical distribution of barium in Tomini Basin indicates that its sedimentary environment has a high palaeo-productivity.